2019
DOI: 10.3389/fpsyg.2019.01355
|View full text |Cite
|
Sign up to set email alerts
|

Executive Processes Underpin the Bilingual Advantage on Phonemic Fluency: Evidence From Analyses of Switching and Clustering

Abstract: Bilinguals often show a disadvantage in lexical access on verbal fluency tasks wherein the criteria require the production of words from semantic categories. However, the pattern is more heterogeneous for letter (phonemic) fluency wherein the task is to produce words beginning with a given letter. Here, bilinguals often outperform monolinguals. One explanation for this is that phonemic fluency, as compared with semantic fluency, is more greatly underpinned by executive processes and that bilinguals exhibit bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 126 publications
(230 reference statements)
1
18
0
Order By: Relevance
“…29 It is noteworthy that several studies have shown that bilingual speakers perform better than monolingual speakers do in phonemic fluency tasks. 30 Moreover, we assume that the verbal comprehension deficits of our patient and other patients with HPCA-related dystonia can be explained by impaired executive functioning as verbal comprehension is suggested to depend on intact working memory functions. 31 Interestingly, we observed impaired working memory functions measured by the WAIS-IV, but only partially impaired executive functions measured by the TAP subtests, whereas performance on other tasks measuring executive functions was normal.…”
Section: Discussionmentioning
confidence: 80%
“…29 It is noteworthy that several studies have shown that bilingual speakers perform better than monolingual speakers do in phonemic fluency tasks. 30 Moreover, we assume that the verbal comprehension deficits of our patient and other patients with HPCA-related dystonia can be explained by impaired executive functioning as verbal comprehension is suggested to depend on intact working memory functions. 31 Interestingly, we observed impaired working memory functions measured by the WAIS-IV, but only partially impaired executive functions measured by the TAP subtests, whereas performance on other tasks measuring executive functions was normal.…”
Section: Discussionmentioning
confidence: 80%
“…In 16 studies (Anderson et al., 2017; Bennett & Verney, 2019; Blumenfeld et al., 2016; Keijzer & Schmid, 2016; Marsh et al., 2019; Morrison et al., 2019, 2020; Portocarrero et al., 2007; Rosselli et al., 2000, 2002; Sadat et al., 2016; Seçer, 2016; Soltani et al., 2021; Taler et al., 2013; Vega‐Mendoza et al., 2015; Zeng et al., 2019) no significant differences emerged between monolingual and bilingual participants.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Marsh et al., 2019; Patra et al., 2020) divided into clusters the words produced by the participants, following the method used by Troyer et al. (1997), and found that bilinguals had a larger cluster size than monolinguals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These verbal fluency deficits must be distinguished from a rather fair performance in simpler tasks of lexical retrieval such as picture naming (e.g., Al-Uzri et al, 2004 ; Tan and Rossell, 2017 ; but see Vogel et al, 2009 ). Thus, rather than assuming the locus of the effect (only) in lexical access per se (e.g., Heim, 2020 ), a link to other cognitive functions such as executive functions (e.g., working memory; processing speed) must be considered as potential causes for these specific deficits in schizophrenia ( Ojeda et al, 2008 ; Berberian et al, 2016 ), as these functions are associated with verbal fluency and cognitive reserve in neurotypical persons and (at least in male) PwS ( Marsh et al, 2019 ; Kubota et al, 2022 ). Also, the dissociation of verbal fluency deficits but no speech-onset latency effects in sentence production is in line with observations in real PwS vs. healthy controls ( Creyaufmüller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%